PREPARATION OF LAYERED MATERIAL Zn/Al-LAYERED DOUBLE HYDROXIDE-FERULATE NANOCOMPOSITES - Muda, Zuhailimuna; Hashim, Norhayati; Md Isa, Illyas; Mohd Ali, Noorshida; Abu Bakar, Suriani; Kamari, Azlan; Mohamed, Azmi (Faculty of Mathematics and Natural Science, Universitas PGRI Palembang, 2016)
A new layered material-drug nanocomposite namely, Zn/Al-layered double hydroxide-ferulate (Zn/Al-LDH-FA) has been synthesized using the ion exchange method. PXRD pattern and elemental analysis showed that Zn/Al-LDH-FA nanocomposite yielded high crystalline and pure phase material with a basal spacing of 17.4 Ã and anion loading of 35.9 % respectively. The FTIR spectra reveal the presence of FA in the interlayer of Zn/Al-LDH, while the thermal analysis shows that the Zn/Al-LDH has enhanced the thermal stability of FA in the interlayer compared to its pure form. Anionic FA intercalated into the interlayer of Zn/Al-LDH as vertical monolayer with the carboxylate groups pointing towards the Zn/Al-LDHs layers. The intercalation of FA into the interlayer of Zn/Al-LDH is also supported by morphology analysis, FESEM.Keywords: Synthesis, Intercalation, Layered Double Hydroxide, Ferulic AcidABSTRAKSebuah bahan-obat berlapis nanokomposit baru yaitu, Zn/Al-berlapis ganda hidroksida-ferulate (Zn/Al-LDH-FA) telah disintesis dengan menggunakan metode pertukaran ion. Pola PXRD dan analisis unsur menunjukkan bahwa Zn/Al-LDH-FA nanokomposit menghasilkan kristalinitas tinggi dan material fase murni dengan jarak basal dari 17,4 Ã dan pemuatan anion 35,9%. Spektrum FTIR mengungkapkan adanya FA di lapisan Zn/Al-LDH, sedangkan analisis termal menunjukkan bahwa Zn/Al-LDH telah meningkatkan stabilitas termal FA di antar lapisan dibandingkan dengan bentuk murninya. Anionik FA diselingi ke dalam interlayer Zn/Al-LDH sebagai monolayer vertikal dengan gugus karboksilat menunjuk ke arah lapisan Zn/Al-LDHs. Interkalasi dari FA ke dalam interlayer Zn/Al-LDH juga didukung oleh analisis morfologi, FESEM.Kata kunci: Sintesis, interkalasi, hidroksida berlapis ganda, asam ferulic